Response of guava (Psidium guajava) genotypes to air-layering under sub-humid southern Rajasthan (Current Horticulture, 2024)
The evaluation of genotypes of guava (Psidium guajava L.) for air-layering under sub- humid southern plains of Rajasthan conditions  was done during July 2015-16 at RCA, MPUAT, Udaipur, Rajasthan. The study involved a diverse set of genotypes, including L-49,  Allahabad Safeda, Lalit, Red Fleshed, Pant Prabhat, Safed Jam, Arka Amulya, Arka Mridula, MPUAT S-1, MPUAT S-2, Shweta,  Burfkhan, Sarbati, RCGH-1, and One-Kg. The results revealed significant variation among the genotypes in terms of their rooting  characteristics. The genotype Lalit stood out, exhibiting the earliest root initiation, the highest percentage of rooted air-layers, the  greatest survival percentage, and the highest vigour index, while number of secondary roots was highest in L- 49 and root: shoot  ratio in Shweta. On the other end of the spectrum, the genotype One-Kg showed a poor response to rooting, making it less ideal for  air-layering propagation under the tested conditions. Thus, genotype Lalit is particularly well-suited for propagation through air layering under sub-humid southern Rajasthan.
Keywords: Chinese layering performance; Sub-humid condition; Red and white fleshed genotypes; Air-layering